2021
DOI: 10.1186/s40359-021-00704-5
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the relationship between parenting style and chronic pain in adolescents: a structural equation modelling approach

Abstract: Background Although the context of parenting has been incorporated into psychosocial pain research, very little attention has been paid to how parenting styles influence chronic pain in adolescents. The present study aimed to investigate the mediating role of self-esteem, emotional intelligence, and psychological distress in the association between parenting styles and chronic pain. Method Seven hundred and thirty nine adolescents and their parents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…In the end, 1302 people (Mean age: 16.87 ± 1.94) participated in the current study due to participant dropouts. Because of an insufficient power and sample size has consequences on statistical tests [ 48 ], power analysis for the correlation tests has conducted with G-Power analysis software (version 3.1.3) [ 49 ] in order to assure us that the size of the sample is adequate to detect a medium (0.30) effect size (q = 0.30) with a power of 0.95 (α = 0.05, 1 – β = 0.95) [ 27 , 50 ].…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…In the end, 1302 people (Mean age: 16.87 ± 1.94) participated in the current study due to participant dropouts. Because of an insufficient power and sample size has consequences on statistical tests [ 48 ], power analysis for the correlation tests has conducted with G-Power analysis software (version 3.1.3) [ 49 ] in order to assure us that the size of the sample is adequate to detect a medium (0.30) effect size (q = 0.30) with a power of 0.95 (α = 0.05, 1 – β = 0.95) [ 27 , 50 ].…”
Section: Methodsmentioning
confidence: 99%
“…In supporting this model, Cunningham et al showed that child pain catastrophizing mediates the relationship between the parental factors such as parental encouragement and monitoring or parental protection with functional abdominal pain-related disability levels [ 32 ]. Similarly, in our recent study on a different sample of adolescents, it has been shown that emotional functioning (including emotional intelligence and psychological distress) significantly mediated the effects of authoritative and authoritarian parenting styles on chronic pain [ 27 ].…”
Section: Introductionmentioning
confidence: 90%
See 3 more Smart Citations